Biofouling hydroids (Cnidaria: Hydrozoa) from a Tropical Eastern Pacific island, with remarks on their biogeography. Issue 9 (19th March 2022) - Calder, Dale R.; Carlton, James T.; Keith, Inti; Ashton, Gail V.; Larson, Kristen; Ruiz, Gregory M.; Herrera, Esteban; Golfin, Geiner
ABSTRACT: The hydroids of Cocos Island (Isla del Coco), Costa Rica, have received scant attention and are poorly known. Only 11 species have been reported from there previously, with five of them being stylasterids. Hydroids examined here were collected during 2019 in a search for invasive species, as part of a fouling survey. Fourteen species – three anthoathecates and 11 leptothecates – were identified in the collection. All represent new records for Cocos Island, elevating its number of reported species to 25. The most abundant species in the collection were Clytia obliqua (Clarke, 1907) and Sertularella affinicostata Calder and Faucci, 2021, found in 11 of 42 samples (26%), and Tridentata borneensis Billard, 1925a, present in nine (21%) of them. Nematocysts of Corydendrium flabellatum Fraser, 1938a and Eudendrium cf. certicaule Fraser, 1938a are newly identified, measured and illustrated. Three species ( Clytia brevithecata (Thornely, 1900), Halopteris alternata (Nutting, 1900) and Macrorhynchia philippina Kirchenpauer, 1872), are introduced, with the rest assigned to a native or cryptogenic status.